History as a boundary object: historiographical reasoning and the politics of climate future (Revista Tempo e Argumento, 2026)
This article examines how historical reasoning shapes the imagination of climate futures by comparing two interventions: an institutional adaptation-pathways exercise developed for the Dutch Cultural Heritage Agency and participatory workshops conducted within the transnational Soy Stories project in Brazil and the Netherlands. While both address climate uncertainty, they mobilize history in markedly different ways. The adaptation-pathways approach made relocation, selective preservation, documentation and planned loss available for institutional discussion, but did so through an expert-led planning format that organized futures through linear sequencing, preservation-oriented categories and institutional assumptions about value and responsibility. By contrast, the workshops introduced historical narratives at the outset as a methodological provocation, treating history as a boundary object through which participants co-produced alternative futures rooted in plural memories, multispecies relations and situated experiences of environmental change. Drawing on environmental history, memory studies and critical heritage scholarship, the article conceptualizes this second approach as a historiographical intervention: a practice that reconfigures how pasts, presents and futures are related in climate adaptation debates. Comparative analysis shows that introducing history as a generative rather than contextual element expands imaginable futures, redistributes narrative authority and exposes normative assumptions embedded in institutional planning tools. The article argues that climate adaptation is not solely a technical challenge but also a historiographical problem requiring more reflexive, plural and socially grounded forms of future-making under climate crisis
Keywords: climate adaptation; historiography; cultural memory; heritage studies; future imaginaries